Evaluation of transmission capacity of houseflies and cockroaches for pathogenic human intestinal parasites - J. Patil, Ashok (International Journal Of Community Medicine And Public Health, 2023)
Background: Household insects like houseflies and cockroaches are found in close proximation with human and animal habitations. These insects act as mechanical vectors for medically important pathogens and parasites. The present study aimed to identify the presence of human intestinal parasites transmitted by these insects in the present study area. Methods: Collection of these insects were carried out for a period of six months (June to November, 2021) from areas like kitchen, college canteen, garbage piles, fish and meat shops. Microscopic examination showed presence of pathogenic human intestinal parasites and pathogens. Results: Of the total collected flies and cockroaches, 157 (61.3%) flies and 72 (52.2%) cockroaches were found to be carriers of medically important parasites and pathogens. A total of three protozoan (Giardia intestinalis, Entamoeba histolytica and Balantidium coli) and three helminth parasites (Ascaris lumbricoides, Enterobius vermicularis and hookworm) were isolated from these insects. The most common protozoan and helminth parasites were Giardia intestinalis and Ascaris lumbricoides. There is significant difference between number of protozoan and helminth parasite on a single housefly and cockroach. Similarly, females of both the insect were found to be more vectorial than males. There was also correlation between the incidence of diarrhea and gastrointestinal tract infection and number of positive flies. Conclusion: These findings imply that both insects in the current study area should be considered as possible mechanical vectors of human intestinal parasites.